Feedback control of prion formation and propagation by the ribosome‐associated chaperone complex. Issue 3 (11th March 2015) - Kiktev, Denis A.; Melomed, Mikhail M.; Lu, Caroline D.; Newnam, Gary P.; Chernoff, Yury O.
Summary Cross‐beta fibrous protein aggregates (amyloids and amyloid‐based prions) are found in mammals (including humans) and fungi (including yeast), and are associated with both diseases and heritable traits. The Hsp104/70/40 chaperone machinery controls propagation of yeast prions. The Hsp70 chaperones Ssa and Ssb show opposite effects on [PSI+], a prion form of the translation termination factor Sup35 (eRF3). Ssb is bound to translating ribosomes via ribosome‐associated complex (RAC), composed of Hsp40‐Zuo1 and Hsp70‐Ssz1. Here we demonstrate that RAC disruption increases de novo prion formation in a manner similar to Ssb depletion, but interferes with prion propagation in a manner similar to Ssb overproduction. Release of Ssb into the cytosol in RAC‐deficient cells antagonizes binding of Ssa to amyloids. Thus, propagation of an amyloid formed because of lack of ribosome‐associated Ssb can be counteracted by cytosolic Ssb, generating a feedback regulatory circuit. Release of Ssb from ribosomes is also observed in wild‐type cells during growth in poor synthetic medium. Ssb is, in a significant part, responsible for the prion destabilization in these conditions, underlining the physiological relevance of the Ssb‐based regulatory circuit.